Trends in online searching toward suicide pre-, during, and post the first wave of COVID-19 outbreak in China - Chen, Hongguang; Zhang, Konglai; Li, Hui; Li, Mengqian; Li, Shunfei (Frontiers in Psychiatry, 2022)
COVID-19 may increase the risk of suicide, but the conclusion is still unclear. This study was designed to assess the impact of COVID-19 on suicide pre-, during, and post the first wave of COVID-19 in China. It was reported that online public searching was associated with their offline thoughts and behaviors. Therefore, this study was designed to explore the online search for suicide pre-, during, and post-COVID-19 in China. The keywords on suicide, COVID-19, unemployment, and depression were collected in 2019 and 2020 using the Baidu Search Index (BSI). A time-series analysis examined the dynamic correlations between BSI-COVID-19 and BSI-suicide. A generalized estimating equation model was used to calculate the coefficients of variables associated with the BSI-suicide. The BSI-suicide showed a significant increase (15.6%, p = 0.006) from the 5th to 9th week, which was also the point of the first wave of the COVID-19 outbreak. A time-series analysis between BSI-suicide and BSI-COVID-19 showed that the strongest correlation occurred at lag 1+ and lag 2+ week. In the pre-COVID-19 model, only BSI-depression was highly associated with BSI-suicide (β = 1.38, p = 0.008). During the COVID-19 model, BSI-depression (β = 1.77, p = 0.040) and BSI-COVID-19 (β = 0.03, p < 0.001) were significantly associated with BSI-suicide. In the post-COVID-19 model, BSI depression (β = 1.55, p = 0.010) was still highly associated with BSI-suicide. Meanwhile, BSI-unemployment (β = 1.67, p = 0.007) appeared to be linked to BSI-suicide for the first time. There was a surge in suicide-related online searching during the early stage of the first wave of the COVID-19 outbreak. Online suicide search volume peaked 1–2 weeks after the COVID-19 peak. The BSI of factors associated with suicide varied at different stages of the COVID-19 pandemic. The findings in this study are preliminary and further research is needed to arrive at evidence of causality.